Murine polyomavirus and simian virus 40 large T antigens produce different structural alterations in viral origin DNA. - Bhattacharyya, S (1995)
Murine polyomavirus (Py) and simian virus (SV40) encode homologous large T antigens (T Ags) and also have comparable sequence motifs in their core replication origins. While the ability of SV40 T Ag to produce specific distortions within the SV40 core replication origin (ori) in a nucleotide-dependent fashion has been well documented, little is known about related effects of Py T Ag on Py ori DNA. Therefore, we have examined viral origin DNA binding in the presence of nucleotide and the resulting structural changes induced by Py and SV40 T Ags by DNase I footprinting and KMnO4 modification assays. The structural changes in the Py ori induced by Py T Ag included sites within both the A/T and early side of the core origin region, consistent with what has been shown for SV40. Interestingly, however, Py T Ag also produced sites of distortion within the center of the origin palindrome and at several sites within both the early and late regions that flank the core ori. Thus, Py T Ag produces a more extensive and substantially different pattern of KMnO4 modification sites than does SV40 T Ag. We also observed that both T Ags incompletely protected and distorted the reciprocal ori region. Therefore, significant differences in the interactions of Py and SV40 T Ags with ori DNA may account for the failure of each T Ag to support replication of the reciprocal ori DNA in permissive cell extracts.